The Changing Confidence Relationship Between the UK Executive and Parliament in Comparative Context. Issue 1 (23rd August 2019) - Schleiter, Petra; Evans, Georgina
Abstract: Executive–legislative relations in the UK are undergoing a process of transformation, and the confidence relationship is part of that change. The confidence relationship not only ensures that the executive is responsible to the legislature, but it also structures bargaining between government and the legislature via the parliament-initiated vote of no confidence and the executive-invoked vote of confidence. The Fixed-term Parliaments Act 2011 changes this relationship by removing from the prime minister the power to call an early election should confidence be lost, and by introducing one formal way of wording no-confidence and confidence motions. We place these changes in comparative context, showing that they strengthen parliament vis-à-vis the government, and discuss their implications against the background of contemporary constitutional practice in developed parliamentary democracies, medium-term electoral and political trends in the UK, and the 2019 Brexit deadlock.